Nanomedicine-based immunotherapy for central nervous system disorders - Hanif Sumaira; Muhammad Pir; Chesworth Rose; Rehman Fawad Ur; Qian Rong-jun; Zheng Meng; Shi Bing-yang (Acta Pharmacologica Sinica, 2020)
Central nervous system (CNS) disorders represent a broad spectrum of brain ailments with short- and long-term disabilities, and nanomedicine-based approaches provide a new therapeutic approach to treating CNS disorders. A variety of potential drugs have been discovered to treat several neuronal disorders; however, their therapeutic success can be limited by the presence of the blood-brain barrier (BBB). Furthermore, unique immune functions within the CNS provide novel target mechanisms for the amelioration of CNS diseases. Recently, various therapeutic approaches have been applied to fight brain-related disorders, with moderate outcomes. Among the various therapeutic strategies, nanomedicine-based immunotherapeutic systems represent a new era that can deliver useful cargo with promising pharmacokinetics. These approaches exploit the molecular and cellular targeting of CNS disorders for enhanced safety, efficacy, and specificity. In this review, we focus on the efficacy of nanomedicines that utilize immunotherapy to combat CNS disorders. Furthermore, we detailed summarize nanomedicine-based pathways for CNS ailments that aim to deliver drugs across the BBB by mimicking innate immune actions.